Using immunization registry data to explore initiation of HPV vaccination at ages 9 and 10 - Grace W. Ryan; Amanda Kahl; Emily Janio; Bethany Kintigh; Don Callaghan; Natoshia M. Askelson (Human Vaccines & Immunotherapeutics)
Despite evidence highlighting benefits of age 9/10 initiation of human papillomavirus (HPV) vaccination, little is known about who is initiating the series earlier. We describe the population of children who initiate earlier and assess the relationship of earlier initiation with series completion. We used individual-level immunization registry data from Iowa which contained data on male (49.9%) and female (50.1%) children born between 2004–2013 ages 9 and 17. We compared sociodemographic characteristics using chi-square statistics and used logistic regression to assess odds of initiation. Of children with a record of HPV vaccination, only 3.2% initiated early. In comparison to children who initiated at later, the early initiator group had a higher percentage of females (p < .0001), greater representation of nonwhite children (p < .0001), higher percentage living in urban areas (p < .0001) and higher private insurance (p < .0001). In logistic regression models, earlier initiation was significantly associated with higher rates of on-time completion (OR: 10.8 (8.6, 13.5)). These results can support prioritization of efforts to promote earlier initiation. For example, rural areas may need targeted outreach. Future work could integrate geospatial analyses so that local organizations could be able to target specific counties or even zip codes with the lowest rates of initiation.